Epidemi Penyakit Tumor pada Sengon (Paraserianthes falcataria) di Jawa Timur, Indonesia - Soekadar Wiryadiputra (Jurnal Ilmu Kehutanan, 2007)
Gall Rust Disease Epidemic on sengon (Paraserianthes falcataria) in East java, IndonesiaIn the early of 2005 at one of the coffee and cocoa estates in the district of Banyuwangi, East Java, an epidemic outbreak of gall disease on albizia (Paraserianthes falcataria) with heavy infestation level occurred. Arthropod pest initially was suspected as the causing agent of the gall. However, intensive observations in the field and laboratory revealed that the gall was caused by the rust fungus of Uromycladium tepperianum. It was a new outbreak of the disease reported in Indonesia.Observation at one division of the estate showed that the extent of albizia trees infected by the pathogen reached to more than 50%. There was an indication that environmental factors especially rainfall and humidity strongly increased the disease intensity and sporulation of the fungus. Results on the fungicide trial conducted in the field indicated that spraying of the mixed solution of Carbendazim (Delsene MX 80 WP) and Flusilazol (Nustar 400 EC) at the concentration of 1 g and 0.3 ml formulation per liter of water respectively was very effective in suppressing the infestation. These mixed fungicides could suppress the disease infestation to 60.1% compared with untreated trees.